Step
*
2
1
1
1
1
of Lemma
rsqrt2-repels-rationals
1. n : ℕ+
2. m : ℤ
3. (2 * m) ≤ (3 * n)
4. (|(r(n) * rsqrt(r(2))) - r(m)| * |(r(n) * rsqrt(r(2))) + r(m)|) = r(|(2 * n * n) - m * m|)
5. n ≤ m
⊢ (r1/r(3 * n * n)) ≤ |rsqrt(r(2)) - (r(m)/r(n))|
BY
{ Assert ⌜r1 ≤ r(|(2 * n * n) - m * m|)⌝⋅ }
1
.....assertion..... 
1. n : ℕ+
2. m : ℤ
3. (2 * m) ≤ (3 * n)
4. (|(r(n) * rsqrt(r(2))) - r(m)| * |(r(n) * rsqrt(r(2))) + r(m)|) = r(|(2 * n * n) - m * m|)
5. n ≤ m
⊢ r1 ≤ r(|(2 * n * n) - m * m|)
2
1. n : ℕ+
2. m : ℤ
3. (2 * m) ≤ (3 * n)
4. (|(r(n) * rsqrt(r(2))) - r(m)| * |(r(n) * rsqrt(r(2))) + r(m)|) = r(|(2 * n * n) - m * m|)
5. n ≤ m
6. r1 ≤ r(|(2 * n * n) - m * m|)
⊢ (r1/r(3 * n * n)) ≤ |rsqrt(r(2)) - (r(m)/r(n))|
Latex:
Latex:
1.  n  :  \mBbbN{}\msupplus{}
2.  m  :  \mBbbZ{}
3.  (2  *  m)  \mleq{}  (3  *  n)
4.  (|(r(n)  *  rsqrt(r(2)))  -  r(m)|  *  |(r(n)  *  rsqrt(r(2)))  +  r(m)|)  =  r(|(2  *  n  *  n)  -  m  *  m|)
5.  n  \mleq{}  m
\mvdash{}  (r1/r(3  *  n  *  n))  \mleq{}  |rsqrt(r(2))  -  (r(m)/r(n))|
By
Latex:
Assert  \mkleeneopen{}r1  \mleq{}  r(|(2  *  n  *  n)  -  m  *  m|)\mkleeneclose{}\mcdot{}
Home
Index